Cultural Pride and Its Impediment in Cross and Multicultural Workspaces - Odorige (The Journal of Society and Media, 2024)
The search for cultural expertise capable of laying bare cultural biases that impede equable interaction in cross and multicultural workspaces has yielded theories such as cultural humility, cultural intelligence, cultural competence, and cultural reflexivity. These theories propose new ways of interaction in groups outside our origin cultures, where culturally institutionalized banalities resulting from our origin culture can be reduced in cross and multicultural settings. This study examines the use of pride in reinforcing culture and its impact on employee relationships in multicultural workspaces. It distinguishes between authentic and hubristic pride and highlights that cultural differences can pose a challenge. To conduct cultural research, pride needs constant review as it is a universal neurocomputational program designed to orchestrate cognition, physiology, and behavior. This inevitable challenge drives the need for competencies in cultural humility, competence, and reflexivity to taper situations of cultural diversity where ideas are contrary. We propose the development of global tribal village workspace communication, holding a more expansive room for valuation with a focus on respect for the sensibilities of others and eschewing quick judgments that bring about incidences of disharmony.